P014 COMPARATIVE EFFECTIVENESS OF RESORBABLE SYNTHETIC ONLAY AND BIOLOGIC INTRAPERITONEAL MESH FOR ABDOMINAL WALL RECONSTRUCTION: A 2-YEAR MATCHED PAIR ANALYSIS. (25th November 2021) - Othman, Sammy; Christopher, Adrienne; Patel, Viren; Jia, Hanna; Mellia, Joseph; Kovach, Stephen; Fischer, John
Abstract: Aim: The literature currently lacks comparative studies examining the relative effectiveness of anatomic planes and mesh selection when combating abdominal wall reconstruction (AWR), particularly when the retrorectus sublay space is not available. The aim of this study was to examine the efficacy of resorbable synthetic mesh onlay (RSOM) plane against biologic mesh in the intraperionteal plane (BIPM). Methods: A single center, two surgeon, 5-year retrospective review (2014-2019) was performed examining subjects who underwent AWR in the onlay plane with resorbable synthetic mesh or the intraperitoneal plane with biologic mesh. A matched paired analysis was conducted. Data examining demographic characteristics, intraoperative variables, post-operative outcomes, and costs were analyzed. Results: A total of 88 subjects (44 per group) were identified (median follow-up: 24.5 months). The mean age was 57.7 years, with a mean BMI of 30.4 kg/m 2 . The average defect size was 292 ± 237 cm 2, with most wounds being clean-contaminated (48.9%), and 55% having prior failed repair. RSOM subjects were significantly less likely (4.5%) to experience recurrence compared to BIPM (22.7%; p <0.026.). Additionally, RSOM suffered less post-operative surgical site occurrences (18.2% vs. 40.9% ;p <0.019) and required fewer procedural interventions (11.4% vs. 36.4% ;p <0.011). RSOM was also associated with significantly less total costs ($16, 658 ± 14, 930) compared to BIPM ($27, 645 ± 16, 864; p <0.001). Conclusion: When faced with hernia repair, the selection of resorbable synthetic mesh in the onlay plane may be preferable to biologic mesh place in the intraperitoneal plane due to lower long-term recurrence rates, surgical site complications, and costs.